Bioactive hybrid membrane-based cellulose acetate/bioactive glass/hydroxyapatite/carbon nanotubes nanocomposite for dental applications. (May 2023) - Al-Harbi, Nuha; Hussein, Mahmoud A.; Al-Hadeethi, Yas; Felimban, Raed I.; Tayeb, Hossam H.; Bedaiwi, Nada M.H.; Alosaimi, Abeer M.; Bekyarova, Elena; Chen, Mingguag
Abstract: The present work aimed to fabricate a set of hybrid bioactive membrane in the form of bio-nanocomposite films for dental applications using the casting dissolution procedures. The formulation of the targeted materials was consisting of cellulose acetate/bioactive glass/hydroxyapatite/carbon nanotubes with a general abbreviation CA-HAP-BG-SWCNTs. The nanocomposites were characterized using XRD, FTIR, SEM-EDX and Raman spectroscopy. XRD, FTIR and SEM characters confirm the nanocomposites formation with good compatibility. The fabricated materials had a semi crystalline structure. The mechanical and thermal properties, as well as contact angle and bioactivity of the fabricated nanocomposites were investigated. The SEM images for showed beehive-like architectures with a thicker frame for the second material. All fabricated materials showed good thermal behaviors. Furthermore, the agar diffusion antimicrobial study showed that the prepared nanocomposites do not exhibit an antibacterial activity against five pathogenic bacterial strains. Additionally, cytotoxicity of a dental nanocomposite filling agent was evaluated. Vero normal cells were incubated with test materials for 72h at 37 °C and 5% CO2 . Cell viability was detected using a SRB assay. All nanocomposites were mildly to non-cytotoxic to Vero cells at high concentration in contrast to the inhibitory effect of doxorubicin which was added at 10-fold lower concertation than the nanocomposites. Hence, the proposed nanocomposite is promising candidates for dental applications. Graphical abstract: Image 1 Highlights: Bioactive hybrid membrane based-nanocomposites as promising candidates for dental applications. Bioactive hybrid membrane-based cellulose acetate/bioactive glass/hydroxyapatite/carbon nanotubes nanocomposites. The cytotoxicity of a dental nanocomposite filling agent has been also investigated. Vero normal cells were incubated with test materials. Cell viability was detected using a SRB assay. Nontoxic products have been displayed in contrast to the inhibitory effect of doxorubicin.